DANGEROUS PORNOGRAPHIC CONTENT ON THE INTERNET AS A PROJECTION OF A PERSONALITY DEVIATION OF THE CHILD PORNOGRAPHY DISTRIBUTOR - Serhii V. Demedyuk; Tetyana S. Demedyuk (Інформаційні технології і засоби навчання, 2018)
The article reveals the issues of danger to Internet users from pornographic content, which is defined as a specific activity projection of a personality deviation of the distributor of child pornography. An analysis of reference sources indicates that the cognitive sphere of child pornography distributor in information networks distincts from those with pedophilic inclinations may be sufficiently developed and should be reflected in the destructive tendencies of their personal dynamics and actions in a specific way. The object of the article is to identify the specifics of information-dangerous pornographic content on the Internet as a projection of personality deviation of the ICT user who produces and distributes child pornography. In the course of the empirical study it was used the semantic analysis techniques of the findings of forensic psychiatric examinations towards those who depraved minors, as well as those who decoyed minors, produced and distributed child pornography in the Internet. Quantitative indexes of psychological variables were established in accordance with nominative and order scales. Empirical data was processed using nonparametric statistical methods. The studies research has been found that ICT user who depraves minors, produces and distributes child pornography in the Internet, along with the necessary development of intelligence, cognitive abilities and sufficient self-organization of cognitive processes is capable of a progressive disintegration of value-motivational sphere with a sharp increase in selfish consumer motives and conscious systematic contempt for social values. It is proved that such persons’ confrontation of development processes and increasing of destruction at the level of personality structure lead to a significant increase of psychic tension, nervous prostration, progression of neurotic disorders, and increase of repetition offenses. It is noted that information-dangerous pornographic content created and distributed by ICT users on the Internet is emotion-laden, seductive, obtrusive, causing the obsessive attention of the observer, and also tends to extension in future.